ChemInform Abstract: Microwave Synthesis, Characterization and Bio‐Efficacy Evaluation of Novel Chalcone Based 6‐Carbethoxy‐2‐cyclohexen‐1‐one and 2H‐Indazol‐3‐ol Derivatives. Issue 21 (2nd May 2013) - Shakil, N. A.; Singh, Manish K.; Sathiyendiran, M.; Kumar, J.; Padaria, Jasdeep C.
Abstract Derivatives (IIIg) and (IVg) are the most active anti‐fungal agents against Rhizoctonia solani.